Basic category theory - Leinster, Tom. (Cambridge: Cambridge University Press, 2017)
"At the heart of this short introduction to category theory is the idea of a universal property, important throughout mathematics. After an introductory chapter giving the basic definitions, separate chapters explain three ways of expressing universal properties: via adjoint functors, representable functors, and limits. A final chapter ties all three together."--
Categories, functors and natural transformations -- Adjoints -- Interlude on sets -- Representables -- Limits -- Adjoints, representables and limits -- Appendix: Proof of the general adjoint functor theorem.
Includes bibliographical references (pages 174-176) and index.
Keywords: Categories (Mathematics); Categories (Mathematics)